2020
DOI: 10.7759/cureus.11011
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Profile of Children With Sickle Cell Anaemia in Steady State

Abstract: Introduction Sickle cell anaemia (SCA) is an inherited, autosomal recessive condition that results from a mutation in the β-globin gene. Vascular occlusion is the underlying mechanism behind a myriad of complications encountered. This vascular occlusion is primarily caused by the increased tendency of red blood cells (RBC) to adhere to the vascular endothelium, and the activation of platelets and total leucocyte count (TLC), hence the need for a steady-state haematological profile in these patients. Method Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
1
0
0
Order By: Relevance
“…In addition, age of patients did not affect hemoglobin levels significantly. These findings are inconsistent with the observation of previous authors [14] who described low hemoglobin levels in young children and in male patients. Low hemoglobin levels in young children have been also reported by Iheanacho et al [18] and low hemoglobin levels in males have been reported by Abubakar et al [19].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In addition, age of patients did not affect hemoglobin levels significantly. These findings are inconsistent with the observation of previous authors [14] who described low hemoglobin levels in young children and in male patients. Low hemoglobin levels in young children have been also reported by Iheanacho et al [18] and low hemoglobin levels in males have been reported by Abubakar et al [19].…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, the mean WBC count of patients was within normal and most patients had normal WBC counts; however, leukopenia was more frequently seen in females than in males and leukocytosis was reported in 2 cases only. Actually, these findings disagree with the findings of previous authors [14,18,19] who found significant leukocytosis in patients with sickle cell anemia. It has been suggested that steady state of inflammation in patients with sickle cell anemia could explain the rise in WBC count associated with cytokine production [24].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Many studies documented that increased in WBC sickle cell anemia patients such as Harp et al (2021), Ahmed et al,(2017) and Akinbami et al (2012), and this is fully agrees with the results of the current study.The present results indicated a significant increase in PLT in sickle cell anemia patients compared with control group. That's agree with the results of the study ofAliu et al,(2020) andOlaniyi et al,(2014) who reported One-third of those with SCA had thrombocytosis, or an increased platelet count. Thrombocytosis in SCA has a number of different causes, including anemia-induced increased erythropoietin secretion, which has homology with thrombopoietin and leads to thrombopoiesis, as well as functional and/or structural asplenia, which is a feature of SCA.On the other hand, the results of the current study agree with the results of the study of Aliyu et al (2008), Antwi-Boasiako et al (2018) and Akwiwu et al (2020) who reported the higher platelet involvement was caused by more frequent crises and more years of life with sickle cell anemia.…”
supporting
confidence: 92%